Motivación y desempeño laboral en la unidad de recursos humanos del Hospital Regional de Loreto, 2023 - Bardales Villacrez, Frank Leander (2023)
The aim of this research is to find out how motivation and work performance are related in the human resources unit of the regional hospital of loreto, 2023. The study is descriptive with a quantitative approach, and non-experimental design. The survey data was calculated to have a Pearson correlation value of 0.617**, which shows that the study variables have a considerable positive relationship, however, it has a significant degree and a bilateral sigma value (bilateral) of 0.004; as established by the decision rule, Ha will be accepted if the calculated sigma value is less than 0.05. The hypothesis, which states that there is a significant correlation between employee motivation and job performance, is supported by the value achieved.